KAJIAN STOK IKAN SELAIS (Cryptopterus spp) DI PERAIRAN UMUM KABUPATEN KUANTAN SINGINGI - Pareng Rengi; Hamdan Alawi; Sumarto ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
Productivity of Cryptopterus spp (Selais Janggut fish) in Kuantan Singingidistrict has decreased each years. This indicates that Cryptopterus spp extinctconditions and should be a priority for recovery and restocking this fish to freshwater of Kuantan Singingi district. To recovery this fish can be done byaquaculture in cages method and restocking this fish in to freshwater byconsidering the type and environmental conditions in each type of public watersKuantan Singingi. Policy strategy in the management of fish stocks was tomanage of fishing area and by management of the conservation area of fresh waterand development of cage aquaculture program in fresh waters .Keywords: Cryptopterus spp, fish stocking, fresh water